2021
DOI: 10.1111/jcmm.16697
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐7 affects peritoneal ultrafiltration associated with elevated aquaporin‐1 expression via MAPK/ERK pathway in peritoneal mesothelial cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, the expression and role of MMP7 in the dialysate have not been well established. Our previous cross-sectional study had shown that dialysate MMP7 was negatively correlated with UF volume in PD patients [ 19 ]. The reduction of UF volume might be directly related to water retention, leading to the occurrence of CHF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression and role of MMP7 in the dialysate have not been well established. Our previous cross-sectional study had shown that dialysate MMP7 was negatively correlated with UF volume in PD patients [ 19 ]. The reduction of UF volume might be directly related to water retention, leading to the occurrence of CHF.…”
Section: Discussionmentioning
confidence: 99%
“…MMP7 is significantly increased and acts as a noninvasive biomarker of prefibrotic signaling in patients with chronic kidney disease [ 17 , 18 ]. Recently, Yin et al found that MMP7 was highly expressed both in the serum and in the fluid discharged after dialysis in PD patients and could upregulate water channel protein—aquaporins 1 (AQP1), thereby enhancing water reabsorption of peritoneal mesothelial cell [ 19 ]. Thus, highly expressed MMP7 in the peritoneal dialysate might be associated with water transport across the peritoneal membrane and may be related to some clinical complications such as CHF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, animal experiments showed that treating mice with JNK- or ERK-specific inhibitors decreased MMP-7 expression in tumor tissue, suggesting that MMP-7 induction occurs via the activation of JNK and ERK [ 29 ]. In addition, human peritoneal mesothelial cells express MMP-7 molecules via ERK activation [ 30 ]. Stimulating HT-29 cells with IL-1α enhanced their MMP-7 protein secretion via activation of phospho-ERK and phospho-p38 MAPK molecules [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages induced by lipopolysaccharide (LPS) or interferon γ (IFN-γ) have been reported to express elevated levels of TNF-α and matrix metalloproteinase-7 (MMP-7) ( Terri et al, 2021 ). MMP-7 can break down the extracellular matrix by digesting casein, gelatines, fibronectin and proteoglycan ( Yin et al, 2021 ). MMP-7 has also been found to promote pulmonary and renal fibrosis through the facilitation of epithelial mesenchymal transition ( Ke et al, 2017 ).…”
Section: Intercellular Communicationmentioning
confidence: 99%
“…MMP-7 has also been found to promote pulmonary and renal fibrosis through the facilitation of epithelial mesenchymal transition ( Ke et al, 2017 ). Current research only indicates that MMP-7 is associated with the prognosis of peritoneal dialysis ( Yin et al, 2021 ; Xiao et al, 2023 ), and its correlation with peritoneal fibrosis needs further investigation. In addition, it is worth noting that recent evidences point towards an active role of the M1 subtype in the genesis of peritoneal fibrosis ( Terri et al, 2021 ).…”
Section: Intercellular Communicationmentioning
confidence: 99%